2012
DOI: 10.2478/v10019-012-0033-z
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound elastography as an objective diagnostic measurement tool for lymphoedema of the treated breast in breast cancer patients following breast conserving surgery and radiotherapy

Abstract: Background.Lymphoedema of the operated and irradiated breast is a common complication following early breast cancer treatment. There is no consensus on objective diagnostic criteria and standard measurement tools. This study investigates the use of ultrasound elastography as an objective quantitative measurement tool for the diagnosis of parenchymal breast oedema.Patients and methods.The elasticity ratio of the subcutis, measured with ultrasound elastography, was compared with high-frequency ultrasound paramet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(60 citation statements)
references
References 28 publications
(84 reference statements)
2
57
0
1
Order By: Relevance
“…Validity studies of ultrasound elastography on breast tissue after radiation therapy demonstrated an increase in subcutis thickness as expected 101. An early study by Mellor et al100 found high correlations between ultrasound-measured skin thickness and arm circumference ( r = 0.95).…”
Section: Other Diagnostic Measuressupporting
confidence: 56%
“…Validity studies of ultrasound elastography on breast tissue after radiation therapy demonstrated an increase in subcutis thickness as expected 101. An early study by Mellor et al100 found high correlations between ultrasound-measured skin thickness and arm circumference ( r = 0.95).…”
Section: Other Diagnostic Measuressupporting
confidence: 56%
“…7 Ultrasound elastography is another new technique that quantitatively and objectively measures tissue elasticity, but further tests are warranted to determine validity. 41 The most used method of presenting limb circumference or volume change has been the circumference reduction rate calculation. 21 It compares the change in limb circumference while using the normal limb as a baseline, thereby taking into account changes in weight, which might skew results.…”
Section: Assessment and Monitoringmentioning
confidence: 99%
“…16) This blurring, however, was found only in 5% of the images analyzed in the current study, which was much less than the percentage of blurring seen in stage II leg LE (range: 24%-47%). 1) Increased SEG is considered a result of increased cell density and collagen content in the tissue, 17,18) which indicates the presence of nonspecific local inflammation. Since lymph stasis causes chronic inflammation due to uncontrolled responses of macrophages and CD4+ cells, 19,20) it may be reasonable to presume that SEG increases in the extremity with LE without exception.…”
Section: Seg Gradementioning
confidence: 99%